Kebijakan Penegakan Hukum terhadap Tindak Pidana Informasi dan Transaksi Elektronik di Indonesia - Velicya Paulina Kolinug (Juridische : Jurnal Penelitian Hukum, 2024)
Technological developments have resulted in increasingly complex forms of crime or criminal acts in society. Of course, this must be balanced with legal policies so that perpetrators do not allow negligence which could have an impact on the interests of individuals, society and the interests of the state. The author in this research examines legal policies regarding information and electronic transaction in Indonesia. Research was conducted using normative research, juridical and conceptual approaches. The research results show that the existence of Law No. 19 of 2016, which is an amendment to Law No. 11 of 2008 concerning Information and Electronic Transactions, is a positive policy amidst the legal vacuum regarding the resolution of criminal acts using technological means. Even though the Criminal Code was previously used, it was not effective. The policy in the formulation of the ITE Law has included corporations as legal subjects and the use of cumulative punishment for criminals. This can have a fear effect on the community so that it can minimize the occurrence of criminal acts in the ITE sector; Next, the Chief of Police of the Republic of Indonesia issued a Circular Number SE/2/11/2021 concerning Ethical Cultural Awareness to Create a Clean, Healthy and Productive Indonesian Digital Space. The mandate of the Circular is to prioritize the use of restorative justice to reduce overcapacity in correctional institutions.